The anchoring effect—long-term dormancy and genetic population structure. Issue 12 (December 2018) - Sundqvist, Lisa; Godhe, Anna; Jonsson, Per; Sefbom, Josefin
Abstract Understanding the genetic structure of populations is key to revealing past and present demographic and evolutionary processes in a species. In the past decade high genetic differentiation has been observed in many microbial species challenging the previous view of cosmopolitan distribution. Populations have displayed high genetic differentiation, even at small spatial scales, despite apparent high dispersal. Numerous species of microalgae have a life-history strategy that includes a long-term resting stage, which can accumulate in sediments and serve as refuge during adverse conditions. It is presently unclear how these seed banks affect the genetic structure of populations in aquatic environments. Here we provide a conceptual framework, using a simple model, to show that long-term resting stages have an anchoring effect on populations leading to increased genetic diversity and population differentiation in the presence of gene flow. The outcome that species with resting stages have a higher degree of genetic differentiation compared to species without, is supported by empirical data obtained from a systematic literature review. With this work we propose that seed banks in aquatic microalgae play an important role in the contradicting patterns of gene flow, and ultimately the adaptive potential and population dynamics in species with long-term resting stages.